Microbiological assessment of a hospital kitchen before and after Good Manufacturing Practices’ intervention - SILVA, Dionice Capistrano da; OLIVEIRA, Janaina Prieto de; SANTOS, Emanoelli Aparecida Rodrigues; TADIELO, Leonardo Ereno; POSSEBON, Fábio Sossai; PEREIRA, Juliano Gonçalves (Food Science and Technology, 2024)
The aim of this study was to investigate the impact of Good Manufacturing Practices (GMP) on the identification and prevention of bacteria that could pose a risk to patient meals. The study used two GMP checklists and microbiological sampling of bacteria, performed six months apart, to assess the facility’s ability to reduce bacterial counts. The results showed hygiene deficiencies in all areas of the hospital. However, there was a significant improvement in GMP compliance following the implementation of an action plan (p = 0.0234). Before the intervention, 55.55% of the criteria were compliant and after the intervention, 69.63% were compliant. Surfaces involved in raw material handling were identified as the most critical in terms of contamination, with high levels of aerobic mesophilic count, Enterobacteriaceae, and Listeria monocytogenes. The intervention significantly reduced the number of bacteria on these surfaces (p < 0.05). Before, the aerobic mesophilic ranged from 0.00 to 6.34 log CFU/cm², and after, from 0.00 to 4.31 log CFU/cm². Additional testing of incoming materials, food, and hands showed no significant risk. The study highlighted the importance of good hand hygiene, which improved after extensive staff training. The GMP guideline and microbiological characterization of the production areas in the hospital kitchens were essential for understanding and acting on bacterial contamination.